REVITALISASI FUNGSI MASJID DALAM MEMBENTUK LEARNING SOCIETY - Supriyadi, Asep; Ramadhan, Fahmi Izzulhaq; Gunawan, Ardi (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
This study aimed to identify and understand the transformation of the role of the mosque as well as to provide revitalization of the role and function of the mosque. This study uses a qualitative approach whose research uses a naturalistic approach. an approach to understanding understanding related to specific contextual phenomena in terms of the arrangement of objects themselves. In qualitative research, researchers are required to focus more on the basic principles of phenomena that occur in social life, which will be analyzed using existing theories. The results of the research analysis show that the role and function of the mosque has developed from time to time. Among others, in terms of management management, infrastructure, facilities and empowerment of learning society. Thus, this study offers the concept of revitalizing the function and role of the mosque as a whole, such as the role and function of worship, education, economy and social.